Optimization Of The Crew In The Implementation Of The Guard Service To Prevent The Occurrence Of Collision Hazards in KM. TL-IX - Kodrat Alam; Muhammad Mahdi; Rizky Fernanda Bastian (IWJ : Inland Waterways Journal, 2022)
Officer has an important role in processing the motion of the ship when sailing to avoid things that are not desirable to avoid the dangers of collision. Formulation of the problem taken by the author in this thesis is the implementation of the guard service to prevent the occurrence of collision hazards in KM.TL-IX optimization of the use of navigation tools to prevent the occurrence of collision hazards. With qualitative research methods that produce descriptive data, the implementation of the guard service can be described clearly and concretely because the data obtained from direct interviews and supported by library methods that provide a clearer picture of a clearer picture of the information presented. The results obtained by the author during the research is the implementation of the guard service on the ship that has not been done properly because Mualim II undisciplined in carrying out guard duty, lack of attention and sense of responsibility of the Guard officer when carrying out guard duty on the bridge and the use of navigation tools that are not optimal. Discussion of the results of the study is the optimization of guard duty must be applied in accordance with STCW 1978 as amended in 2010, Mualim should also be guided by the Collision Regulation 1972 in the face of situations that allow the danger of collision. The use of navigation equipment as a detection of collision hazards should be able to produce maximum results for the Prevention of collision hazards and to avoid emergencies. In this case, it is concluded that the distribution of guard duty on board KM.TL-IX has been in accordance with regulations set internationally but in practice there are irregularities because the Mualim II is not responsible when carrying out his guard duty, a sense of lack of attention of the Guard officer during the bridge guard service and the use of navigation tools that are less than optimal by the mualim cause the results obtained are not optimal. The advice of the author is a senior Mualim should set an example to other mualim in the implementation of the guard service on schedule and must be carried out in a disciplined manner and the captain and the Mualim must have skills in operating navigation equipment.